Predators of the Alfalfa Aphids Acyrthosiphon pisum (Harris), Aphis craccivora Koch, and Therioaphis trifolii (Monell) (Hemiptera: Aphidoidea) as Determined by the Serological Technique - Cunha, Suzan Beatriz Zambon da; Sousa e Silva, Carlos Roberto; Diniz, Flávio Henrique Góis; Berti-Filho, Evôneo (EntomoBrasilis, 2016)
Predators of the Alfalfa Aphids Acyrthosiphon pisum (Harris), Aphis craccivora Koch,and Therioaphis trifolii (Monell) (Hemiptera: Aphidoidea) as Determined by the Serological Technique Abstract. The serology is an immunological technique based on antigen/antibody reactions in where its main advantages are high sensitivity and specificity that allows the biological recognition at the molecular level. This study evaluates the use of serology technique to determine the predators of the alfalfa aphids Acyrthosiphon pisum (Harris), Aphis craccivora Koch,and Therioaphis trifolii (Monell)(Hemiptera: Aphidoidea). The aphid samplings to obtain the antibodies and their possible predators to be used as antigens were carried out in the alfalfa fields of the Embrapa Pecuária Sudeste Unit, São Carlos, SP. In the period from August 2011 to July 2012. A total of 2,161 arthropod predators, including insects and spiders, were tested. The antibodies obtained for the aphid A. craccivora, A. pisum, and T. trifolii showed partial identity nevertheless still allowed to recognize the predators of alfalfa aphids. Among the insects, syrphids and chrysopids presented the highest percentage of positive results in the serological tests. The species A. craccivora was the most preyed aphid. Determinação de Predadores dos Pulgões da Alfafa Acyrthosiphon pisum (Harris), Aphis craccivora Koch e Therioaphis trifolii (Monell)(Hemiptera: Aphidoidea) por meio da Técnica Serológica Resumo. A serologia é uma técnica imunológica baseada em reações antígeno/anticorpo, em que suas principais vantagens são a alta sensibilidade e especificidade que permitem o reconhecimento biológico em nível molecular. Este trabalho avalia o uso da técnica serológica para determinar os predadores dos pulgões da alfafa, Acyrthosiphon pisum (Harris), Aphis craccivora Koch e Therioaphis trifolii (Monell) (Hemiptera: Aphidoidea). As coletas dos pulgões para a obtenção dos anticorpos e de seus possíveis predadores para serem utilizados como antígenos foram realizadas nos campos de alfafa da Unidade da Embrapa Pecuária Sudeste, São Carlos, SP. no período de agosto de 2011 a julho de 2012. Foram testados 2.161 artrópodes predadores, incluindo insetos e aranhas. Os anticorpos obtidos para os pulgões A. craccivora, A. pisum, e T. trifolii mostraram identidade parcial mas, ainda assim, permitiu reconhecer os predadores dos pulgões da alfafa. Dentre os insetos, sirfídeos e crisopídeos foram os que apresentaram as maiores porcentagens de resultados positivos nos testes serológicos. A. craccivora foi o afídeo mais consumido pelos predadores.